Conflict Resolution - Fred Casmir (Communicare)
TRULY effective and successful human negotiation and the resolution of conflict (also where South Africa is concerned) can only be developed by a process preceding actual negotiation. Destructive tendencies resulting from perceptions or expectations deeply rooted in different cultural backgrounds, can only be overcome through the conscious effort to create a basic, mutually acceptable communication sub-culture in which trust plays a central role. Rather than approaching any given negotiation situation with a fixed, preconceived action model already in mind, communication scholars will have to begin their work much earlier. Individual, social, and cultural components which exist prior to interpersonal communication situations will have to be identified and studied. This approach requires the initial acceptance of complexity, and the ability to allow specific conditions to assist them in discovering and developing situationally appropriate techniques.